Analyzing Madrasah Ibtidaiyah Teacher Candidates Skill of Technological Pedagogical Content Knowledge on Natural Science Learning - Juhji Juhji (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractThis study aims to determine the ability of Technological and Pedagogical Content Knowledge of prospective teachers of primary school at science subject. Respondents of this study were prospective teachers of the primary school in UIN Sultan Maulana Hasanuddin Banten in the academic year 2018/2019 which took the Practice Program Course of Employment in the semester VII. The method used in this study is a type of survey cross-sectional design. The research instruments include a closed questionnaire, analysis of lesson plans, and observation sheet. The data obtained in this study is the description of Technological Pedagogical Content Knowledge at Science Subject. The results showed that the mean skill score technological knowledge prospective teachers primary school of 2.94 (good category), average skill score pedagogical knowledge for prospective teachers primary school is 2.86 (good category), average skill score content knowledge for prospective teachers of primary school is 2.66 (good category), average skill score pedagogical content knowledge prospective teachers of primary school are 3.02 (good category), average skill score technological content knowledge prospective teachers of primary school of 2.41 (a quite good category), average skill score of technological pedagogical knowledge prospective teachers of primary school is 2.65 (good category), average skill score of TPCK prospective teachers of primary school is 2.38 (category pretty good). Thus, it can be concluded that the ability of Technological Pedagogical Content Knowledge Prospective Teachers of Primary School in Science Subjects has a pretty good category.Keywords: prospective teachers of madrasah Ibtidaiyah, science learning, technological pedagogical content knowledge.AbstrakPenelitian ini bertujuan untuk mengetahui kemampuan Technological Pedagogical Content Knowledge calon guru Madrasah Ibtidaiyah pada pembelajaran Ilmu Pengetahuan Alam (IPA). Responden penelitian adalah mahasiswa calon guru Madrasah Ibtidaiyah di UIN Sultan Maulana Hasanuddin Banten tahun akademik 2018/2019 yang mengambil mata kuliah Program Praktik Lapangan Kerja (PPLK) di semester VII. Metode yang digunakan dalam penelitian ini adalah survei dengan tipe cross sectional design. Instrumen penelitian berupa angket tertutup, lembar analisis dokumen RPP, dan lembar observasi. Data yang diperoleh berupa deskripsi tentang Technological Pedagogical Content Knowledge pembelajaran IPA. Hasil penelitian menunjukkan bahwa rata-rata skor keterampilan technological knowledge calon guru Madrasah Ibtidaiyah sebesar 2,94 (kategori baik), rata-rata skor keterampilan pedagogical knowledge calon guru Madrasah Ibtidaiyah sebesar 2,86 (kategori baik), rata-rata skor Keterampilan content knowledge calon guru Madrasah Ibtidaiyah sebesar 2,66 (kategori baik), rerata skor keterampilan pedagogical content knowledge calon guru Madrasah Ibtidaiyah sebesar 3,02 (kategori baik), rata-rata skor keterampilan technological content knowledge calon guru Madrasah Ibtidaiyah sebesar 2,41 (kategori cukup baik), rata-rata skor keterampilan technological pedagogical knowledge calon guru Madrasah Ibtidaiyah sebesar 2,65 (kategori baik), rata-rata skor keterampilan technological pedagogical content knowledge calon guru Madrasah Ibtidaiyah 2,38 (kategori cukup baik). Dengan demikian, dapat disimpulkan bahwa kemampuan Technological Pedagogical Content Knowledge calon guru Madrasah Ibtidaiyah pada pembelajaran IPA memiliki kategori yang cukup baik.Kata kunci: calon guru madrasah ibtidaiyah, pembelajaran ipa, technological pedagogical content knowledge.